Anaerobic Bacteria as a Cause of Mycotic Aneurysm of the Aorta: Microbiology and Antimicrobial Therapy - Brook, Itzhak (Bentham Science Publishers Ltd, 2009)
This review summarizes the microbiology, and antimicrobial management of mycotic aneurysm of the aorta (MAA) due to anaerobic bacteria. Anaerobic bacteria are an uncommon but important cause of MAA. Most cases of anaerobic MAA are caused anaerobic gram-negative bacilli (mostly B. fragilis group), Clostridium spp. (mostly Clostridium septicum, and Propionobacterium spp. (mostly P. acnes). Clostridial infection is frequently associated with gastrointestinal or hematologic malignancy. A review of all the reported cases is presented. Treatment of MAA involving anaerobic bacteria includes the use of antimicrobial effective against these organisms.